IPR and Technological Issues Regarding a Biopharmaceutical Formulation -Hemoglobin - Bansal, Parikshit; Honrao, Chandrashekhar; Banerjee, Uttam C. (Recent Patents on Biotechnology, 2008)
Hemoglobin, the protein responsible for the red color of blood plays a very important part in ‘life’- it transports oxygen, without which humans cannot survive. The idea of using purified Hemoglobin as a possible universal substitute for red blood cells has been around for almost a century. Hemoglobin formulations have important therapeutic applications, especially in case of trauma and war when requirements for blood may be very large. Manufacture of hemoglobin for use as a biopharmaceutical poses practical challenges, owing to dependence on human expired blood and fragility of the protein molecule. Biotechnology can play a critical role in breaking these barriers, by not only ensuring recombinant production of hemoglobin, but also enhancing stability of the molecule. The present article, based on a review of patents and available literature gives an insight into the IPR and technological issues involved in the commercial production of this ‘life-saving’ protein. There are more than 250 patents worldwide related to hemoglobin formulation, crosslinking and determination.
Keywords: biopharmaceutical recombinant formulation